2020
DOI: 10.1155/2020/4176186
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study for Influence of Surfactants Chemical Microstructures on Wetting Effect about Coal Dust in Tongchuan Mining Area

Abstract: Because of the unsatisfactory dust suppression efficiency, coal dust still threatens production safety and personnel health. In order to understand the influence of the chemical microstructures of the surfactant on the wetting ability and to facilitate the rapid selecting of surfactants with good wetting performances for specific coal dust, fatty acid methyl ester ethoxylate (FMEE), dodecyl dimethyl betaine (BS-12), sodium fatty acid polyoxyethylene ether carboxylate (AEC), and dodecyl dimethyl benzyl ammonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…According to Fourier transform infrared spectroscopy (FTIR), Ma et al. 30 and Xu et al 31 investigated the effect of the chemical structure of a surfactant and concluded that hydroxyl is the hydrophilic factor and the aliphatic group is the hydrophobic factor of coal. To better improve the effect of the surfactant on coal wettability, some scholars further studied the internal factors affecting coal wettability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Fourier transform infrared spectroscopy (FTIR), Ma et al. 30 and Xu et al 31 investigated the effect of the chemical structure of a surfactant and concluded that hydroxyl is the hydrophilic factor and the aliphatic group is the hydrophobic factor of coal. To better improve the effect of the surfactant on coal wettability, some scholars further studied the internal factors affecting coal wettability.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al 29 established the evaluation index system of wetting parameters by an analytic hierarchy process and proposed a method to obtain the optimum surfactant concentration for spray dust suppression. According to Fourier transform infrared spectroscopy (FTIR), Ma et al 30 and Xu et al 31 investigated the effect of the chemical structure of a surfactant and concluded that hydroxyl is the hydrophilic factor and the aliphatic group is the hydrophobic factor of coal. To better improve the effect of the surfactant on coal wettability, some scholars further studied the internal factors affecting coal wettability.…”
Section: Introductionmentioning
confidence: 99%